Strengthening Professional and Spiritual Education Through 21st Century Skill Empowerment in a Pandemic and Post-Pandemic Era : Proceedings of the 1st International Conference on Education (ICEdu 2022), September 28, 2022, Malang, Indonesia - Syamsul Arifin; Ahmad Fauzi; Triastama Wiraatmaja; Eggy Fajar Andalas; Nafik Muthohirin (Routledge, 2024)
Discover a treasure trove of knowledge in the proceedings of the First International Confer-ence on Education (ICEdu). This meticulously curated collection of research papers delves into the transformative landscape of education in the 21st century, offering insights, solutions, and inspiration for educators, researchers, and policymakers alike.Explore a diverse range of subject areas, from pedagogical innovations to the challenges of digital learning and the impact of the COVID-19 pandemic on education. With 28 scholarly papers contributed by experts from around the world, this volume offers a comprehensive un-derstanding of the multifaceted issues in contemporary education.Whether you're an academic seeking fresh perspectives or an educator navigating the com-plexities of modern pedagogy, these proceedings provide invaluable guidance. Join us in shap-ing the future of education by harnessing the power of 21st-century skills, professional devel-opment, and spiritual growth.This book is an essential resource for anyone passionate about the advancement of education in the pandemic and post-pandemic era.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Funded by Universitas Muhammadiyah Malang, Indonesia.